From Traditional Marketplace to Online Shop: Shifting Shopping Patterns among University Students in Bangladesh - Balaly, Md. Habibullah; Islam, Md. Rabiul; Makhdum, Niaz; Shah, A.M.M. Mubassher; Banna, Hasanul (Universitas Bina Darma, 2025)
The explosive rise of e-commerce has largely changed shopping habits around the world, and university students are one of the biggest groups to have changed their ways of shopping. In Bangladesh, the change from conventional to digital shopping has been visible with the help of mobile technology, the impact of social media, and also due to the ease of online shopping. The study identifies the drivers of online shopping acceptance among university students in Bangladesh through the lens of theoretical framework based on TAM, UTAUT and TPB. Quantitative method was employed, and the data were collected using simple random sampling from 384 students, determined based on 95% confidence level and 5% margin of error, from three different universities in Bangladesh. The results suggest that the convenience, quickness, and the assortment of the product are the key motivations that drive students to online shopping. Besides, social media networks, mainly Facebook and Instagram, play an incredibly significant role in deciding to buy the students. However, issues like the delay in delivery, high delivery charges, and the question of products' authenticity have proven to be the barriers to the online shopping experience. The research advocates that a reduction in delivery fees, better logistics operations, and providing student discounts will lead to an increase in adoption of e-commerce in Bangladesh. Besides, it is essential to instill customer trust in e-commerce platforms by using secure payment systems and trustworthy products and delivery services.